Performance Analysis at Link Level, for the Next-Generation 802.11N Wi-Fi Channel - Lagos Sandoval, José Arturo; Rodríguez Bejarano, Stephanne; Barragán Vera, Mónica (TECCIENCIA, 2017)
Speed in data networks is affected significantly when the network supports applications that imply real-time data transmission. This degradation is given precisely by the amount of information used in these types of applications and by the data fragmentation process required. Due to this degradation of speed over the network, in recent years, data transmission performance has advanced considerably over the physical links to improve the conditions of quality of service over these applications, mainly because the new skills required in the new data structure makes it necessary to analyze some types of performance improvements. A probabilistic-type mathematical analysis is sought to, first, analyze the type of packet delivery by the Wi-Fi technology described in the 802.11 standard and, thus, seek the possibility of increasing the value of the maximum transfer unit on these networks. The project shows that if the channel capacity is the same, but transmission distance changes, the value of the throughput capacity (T/C) ratio will be the same, only changing the propagation time according to changes in distance and it is concluded that the capacity and distance parameters do not affect the T/C ratio, evidencing that the bit error rate is the key parameter in this relation.